Genome-wide identification and stress-responsive expression profiling of the TCP gene family in Cenchrus fungigraminus under drought and cold stress - Shijie Ke; Xin He; Mengmeng Zhang; Lin Luo; Yuxin Chen; Yixue Cui; Yelin Huang (BMC Genomics)
Abstract Background TCP transcription factors play a crucial role in various biological processes, including plant growth, development, and response to abiotic stress. However, few related studies investigated the characteristics of TCP genes of Cenchrus and how it plays a role in abiotic stress responses. Results Here, we identified 40 CfuTCPs unevenly distributed across 13 chromosomes of Cenchrus fungigraminus and classified them into three subfamilies based on the conserved domain and phylogenetic analysis. Sequence analysis revealed that all CfuTCPs contain basic Helix-Loop-Helix conserved regions, and the majority of the CfuTCP genes were intronless. Twelve genes in the CIN subclade had potential miR319 target sites. Cis-acting element analysis showed that most CfuTCP genes contained many light-, phytohormone-, and developmental stress-responsive elements in their promoter regions. Furthermore, CfuTCPs play an important role in biological activities such as transcription regulation, regulation of biosynthetic processes, and metabolic processes, and were involved in plant circadian rhythms and environmental adaptation pathways. Notably, RNA-seq data showed that most CfuTCPs were involved in stress response under drought and cold treatments. Through RNA-seq analysis and qPCR validation, CfuTCP27/31 were found to play a positive regulatory role in drought stress, while CfuTCP06 plays a negative potentially. Conclusions In total, 40 CfuTCP genes were identified in C. fungigraminus. Functional predictions suggested the roles of CfuTCPs in modulating multiple C. fungigraminus physiological processes and metabolic pathways. The induced expression of CfuTCPs under drought and cold stress indicated their involvement in abiotic stress response in C. fungigraminus. These findings lay the groundwork for further research on TCP genes in C. fungigraminus.